2019
DOI: 10.1016/j.isci.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Adaptation to Years-Long Starvation Resembles that of Bacteria

Abstract: Summary The G rowth A dvantage in S tationary P hase (GASP) phenomenon, described in bacteria, reflects the genetic adaptation of bacteria to stress, including starvation, for a long time. Unlike in stationary phase where no cell division occurs, GASP harbors active cell division, concurrent with genetic adaptation. Here we show that GASP occurs also in eukaryotes. Two strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…In E. coli, the stationary phase period is followed by a type of programed cell death and selection of survivors exhibiting the GASP phenotype 50,51 that results mainly from mutations reducing the activity of the sigma S/ sigma38 transcription factor (RpoS), the general starvation/stressresponse transcriptional regulator 52,53 . Thus, similarly to the relationship previously proposed for the closely linked mTOR pathway 42,54 , the fission yeast S/MAPK pathway plays a function analogous to RpoS in bacteria. This similarity indicates that the stress-response pathways are central to the genetics of quiescence.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In E. coli, the stationary phase period is followed by a type of programed cell death and selection of survivors exhibiting the GASP phenotype 50,51 that results mainly from mutations reducing the activity of the sigma S/ sigma38 transcription factor (RpoS), the general starvation/stressresponse transcriptional regulator 52,53 . Thus, similarly to the relationship previously proposed for the closely linked mTOR pathway 42,54 , the fission yeast S/MAPK pathway plays a function analogous to RpoS in bacteria. This similarity indicates that the stress-response pathways are central to the genetics of quiescence.…”
Section: Discussionsupporting
confidence: 66%
“…In budding yeast, high-throughput screening identified HOG1, SSK2 (SAPK pathway), and SGF73 in glucoseand sulfate-limited conditions, respectively 32,41 . Recently, HOG1 was also found mutated in yeast after a 2-year starvation in sealed 500 750 1000 0 250 500 750 1000 0 250 500 750 1000 0 250 500 750 1000 0 250 500 750 1000 0 250 500 750 1000 0 250 500 750 1000 0 250 500 750 1000 0 250 500 bottles of beer 42 . Thus, mutating the stress-response pathway emerges as a common strategy to promote a growth advantage under different starvation conditions in two unrelated yeast, indicating a high degree of converging evolution 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Looking for evidence of adaptive evolution through convergence of mutations, we found that between experiments, there were 5 genes wherein multiple mutations were observed in the coding sequence between experiments (Table 2). We note that mutations in UBP1, which encodes a ubiquitin protease, were previously identified in experimental evolution of a lager strain [34], and mutations in TFB1, a nucleotide excision repair factor and subunit of TFIIH, were found in strains that had survived for two years in a sealed beer bottle [35]. However, in neither of these cases were phenotypic consequence proven.…”
Section: Resultsmentioning
confidence: 88%
“…We have investigated the adaptation process that S. cerevisiae cells undergo after two years of starvation in a stressful environment of a beer bottle (Aouizerat et al, 2019a). We found striking lines of similarity between characteristics of GASP in bacteria and yeast.…”
Section: Epnp Phase In Eukaryotic Cellsmentioning
confidence: 99%